(untitled) (Research, Society and Development, 2020)
This study aims to understand how Jesuit education occurred in the territory of the Captaincy of São Vicente in the 16th century. The bibliographic search of documentary character analyzed the records made by the Jesuit priests themselves to discuss the role of education in that society. The performance of the priests, in particular the Jesuits, played a decisive role in the formation of culture and education in Brazil. The results and discussions refer to the field of educational history in the Brazilian colony of Portugal that allow updating of studies in the area of history and historiography of education and understand that at that time, education was associated with religion. The contributions of the Acts of the State of São Paulo, together with Jesuit letters, led to the conclusion that the process of institution of education in Brazil, was not an easy task for the Jesuits, but allowed the development of a new way of life for the indigenous people. Still, it is possible to see that education, together with the interests of the Portuguese Crown, allowed the expansion of the Captaincy to develop the political and economic relations of the time.